Beta‐lapachone inhibits pathological retinal neovascularization in oxygen‐induced retinopathy via regulation of HIF‐1α. Issue 5 (18th February 2014) - Park, Sung Wook; Kim, Jin Hyoung; Kim, Ko‐Eun; Jeong, Moon Hee; Park, Hyunsung; Park, Bongju; Suh, Young‐Ger; Park, Woo Jin; Kim, Jeong Hun
Abstract Retinal neovascularization in retinopathy of prematurity (ROP) is the most common cause of blindness for children. Despite evidence that hypoxia inducible factor (HIF)‐1α ‐VEGF axis is associated with the pathogenesis of ROP, the inhibitors of HIF‐1α have not been established as a therapeutic target in the control of ROP pathophysiology. We investigated the hypothesis that degradation of HIF‐1α as a master regulator of angiogenesis in hypoxic condition, using β‐lapachone, would confer protection against hypoxia‐induced retinopathy without affecting physiological vascular development in mice with oxygen‐induced retinopathy (OIR), an animal model of ROP. The effects of β‐lapachone were examined after intraocular injection in mice with OIR. Intraocular administration of β‐lapachone resulted in significant reduction in hypoxia‐induced retinal neovascularization without retinal toxicity or perturbation of developmental retinal angiogenesis. Our results demonstrate that HIF‐1α–mediated VEGF expression in OIR is associated with pathological neovascularization, not physiological angiogenesis. Thus, strategies blocking HIF‐1α in the developing eye in the pathological hypoxia could serve as a novel therapeutic target for ROP.